The impact of new information and communication Technologies (ICTs) in teaching Chinese for special purpose (MSP) on media writing: An action research project - Yap, Teng Teng; Soh, Bee Kwee (2017)
This study aims to explore the perception and attitude of student on the effective use of modern technology such as Information and Communication Technologies (ICTs) in teaching and learning Chinese for Mass Media at tertiary level. Students will explore to mass media writing tasks, such as news writing, interviewing report and journalism writing. Besides, students are requested to produce short video shooting and interviewing with people as well. Through using appropriate ICTs such as Kahoot, Padlet and software include Adobe Premier and Adobe Illustrator to work with images; audio, reporting and shooting via integrative pedagogical, students are encouraged to transform ideas and Information Into Chinese news writing forms through in many multimedia styles and formats. Action research as methodology is applied in the process of teaching and learn Ing. Implement ICTs into curricula and use them effectively in securing students' motivation and positive interaction In addition to providing new ways to learn media writing and the effectiveness on how ICTs can transform education, making it far more Interactive and empowering for students and lecturers. The results of the study showed that the participants have been motivated using ICT in learning Chinese media writing skills in the tertiary education to improve the use of media writing and of that what advantages and challenges the participants have encountered.